Propuesta de clasificación morfologica para los fitolitos altoandinos colombianos (2001)
ABSTRACT: Morphological characteristics of phytoliths are more or less constant in the respective vegetative species, and their tissues serve functions of support, resistance, or defense. Many investigators have proposed classifications for the phytoliths: Ehrenberg (1854), Pratt (1932), Bertoldi de Pomar (1971), Ellis (1979), Mulholland (1986), Piperno (1988), Pearsall & Dinan (1992), Mulholland & Rapp (1992), Twiss (1992), Deflandre (1963), Piperno & Pearsall (1998) y Zucol (1995, 1998). In these publications three general tendencies for the classification of phytoliths are evident: 1) according to the botanical origin of the phytolith; 2) according to the morphology of the phytolith, and 3) combinations of both approaches. The classification proposed here is based strictly on morphological characteristics exhibited by unarticulated phytoliths and partially follows the categories of Bertoldi de Pomar (1971). Of the attributes of the phytoliths, the form is perhaps the most conspicuous element and even though this involves three dimensional bodies with sometimes irregular multiple faces and distinctive dimensions, in the majority of cases, they tend to resemble known and named idealized geometrical forms, and for this reason this characteristic has been amply used in the study of phytoliths. Similarly, the superficial ornamentation of phytoliths is also easily observed and there already exists a widely employed terminology for naming the distinct types present in other microfossils, with its use in palinologia especially clear. The unarticulated phytolith is taken as the fundamental entity in this systematic proposal which only contains three categories: the range of form-genera is the basic unit and is based upon the form and ornamentation; it is employed informally only as a supracategory for grouping the morphogenera, accepting the nomenclature of morphotribes proposed by Bertoldi de Pomar (1971) and infra-categories are reserved to permit the future accommodation of the species. Through this proposal, 19 morphotribes and 77 morphogenera are established.